Transformation of Local Wisdom Values in the Song "Damar Asih Caruban Nagari" - Yahya, Yud’a Yuha; Sunarto, Sunarto (Jurnal Ragam Pengabdian, 2026)
This study examines the transformation of local wisdom values embodied in the song Damar Asih Caruban Nagari, also known as the Gunung Jati song, as a representation of the cultural and spiritual heritage of the Caruban Nagari (Cirebon) community. The study aims to explore the meanings embedded in the song and to analyze how its local wisdom values have been transmitted and implemented within the socio-cultural life of the Cirebon community. Employing a qualitative research approach, data were collected through interviews and document analysis and subsequently analyzed using an interpretive framework. The findings reveal that Damar Asih Caruban Nagari embodies four interconnected dimensions of local wisdom: cultural, moral, religious, and social values. The song contains ethical guidance and authentic Islamic teachings inherited from ancestors and Islamic saints (Wali) of Caruban Nagari, reflecting a harmonious integration of Islamic principles with indigenous cultural traditions. These values continue to function as moral and spiritual guidance for the community while reinforcing collective cultural identity. Consequently, Damar Asih Caruban Nagari represents not only a musical composition but also an enduring symbol of Cirebon's cultural and spiritual heritage, demonstrating the dynamic transformation and continuity of local wisdom across generations.